2021
DOI: 10.22541/au.161530497.73055461/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of the PETase Conformational Changes Induced by Poly(ethylene terephthalate) Binding

Abstract: Recently, a bacterium strain of Ideonella sakaiensis was identified with the uncommon ability to degrade the poly(ethylene terephthalate) (PET). The PETase from I. sakaiensis strain 201-F6 catalyzes the hydrolysis of PET converting it to mono(2-hydroxyethyl) terephthalic acid (MHET), bis(2-hydroxyethyl)-TPA (BHET), and terephthalic acid (TPA). Despite the potential of this enzyme for mitigation or elimination of environmental contaminants, one of the limitations of the use of PETase for PET degradation is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The PCs were obtained from the diagonalization of the covariance matrix obtained from the Cartesian coordinates of the superposed Cα atoms of complex structure. To avoid an underestimate of the atomic displacement, an iterated superposition procedure was applied before the PCA, where residues displaying the largest positional differences were excluded at each round until only the invariant 'core' residues remained [76][77][78][79] .…”
Section: Methodsmentioning
confidence: 99%
“…The PCs were obtained from the diagonalization of the covariance matrix obtained from the Cartesian coordinates of the superposed Cα atoms of complex structure. To avoid an underestimate of the atomic displacement, an iterated superposition procedure was applied before the PCA, where residues displaying the largest positional differences were excluded at each round until only the invariant 'core' residues remained [76][77][78][79] .…”
Section: Methodsmentioning
confidence: 99%
“…We recently studied the reaction mechanism of the PET degradation catalysed by IsPETase and IsMHETase, as well as by the metagenome-derived leaf-branch compost cutinase (LCC-ICCG variant) 15 by computational methods with predicted rate constants in agreement with the experimental observations. 16 The similar mechanism obtained in both systems suggested that the origin of the apparent better performance of LCC-ICCG protein over IsPETase must be due to its thermal stability and its intrinsic relationship with the crystallinity grade of the polymer, which was con rmed by our recent analysis of the structural changes of IsPETase induced by PET binding, 17 and by the results of Alper and co-workers who, based on the structure-based machine learning algorithm, engineered a robust and active PET hydrolase basically by improving its capability of working at a larger range of temperatures and pH levels. 18 The results derived from these computational studies represent the bedrock to understanding the molecular mechanism that rules the performance of PET degrading enzymes.…”
Section: Introductionmentioning
confidence: 64%
“…The electrostatic potential map is a widely used coloring scheme of protein surfaces that indicates the overall charge distribution. [45][46][47][48] Meanwhile, electrostatic maps are predictive of the chemical reactivity of ligands and their types of intermolecular interactions. We analyzed the electrostatic potential map of EiEPSPS wt and EiEPSPS mut to investigate potential affinity sites of the bromine interface of AG332841.…”
Section: Binding Affinities and Dynamic Analyses Of Natural Products ...mentioning
confidence: 99%